THE CONFLICT OF LIBERALISM AND DEMOCRACY - Jokubaitis, Alvydas (Politologija, 2015)
The term “liberal democracy” hides the conflict of two different philosophies. Liberal metaphysics is based on the idea of thing, while democracy is based on the idea of action and process. Democratic process does not have any core of ideas, which is typical of liberalism. The goal of liberal political philosophy is to circumscribe political power. The aim of democracy is the creation of self-government of the citizens. Liberals do not see many things that are important to democrats: common good, community, nation, history and cultural identity. It is possible to speak about fundamental conflict between liberal individualism and general will of democracy. In discussions about democracy there is always at least some confusion about the role of liberalism and democracy. Contemporary theoreticians of democracy do not want to admit that the drawbacks of liberal political philosophy necessarily become the weaknesses of democracy. This is the price we have to pay for the fusion of liberalism and democracy. The drawing of demarcation lines between the spheres of influence of democracy and liberalism today is the main goal of the theory of democracy.